Esophageal caustic injuries in pediatrics: a sobering global health issue - Alser, O; Hamouri, S; Novotny, N (SAGE Publications, 2019)
Caustic material ingestion by children is considered a global healthcare issue, especially in low-to-middle income countries. The aim of this article was to review the epidemiology, prevention, and management of caustic material ingestion in pediatric patients, comparing low-to-middle income countries with high-income countries. We conducted an English literature review using PubMed with the following keywords: (caustic OR corrosive) AND ingestion AND (pediatric OR pediatric). Our search retrieved 253 citations; all abstracts were screened by the authors, and 52 articles were finally included in our review. Prevention is key in tackling this issue, but legislation is scarce in low-to-middle income countries. Diagnosis of caustic ingestion is mostly achieved using flexible endoscopy, computed tomography, and endoscopic ultrasound, but access is limited in low-to middle income countries and diagnosis is often delayed. After stabilizing patients, the mainstay of treatment is graded endoscopic dilatation, and rarely, esophageal replacement. We concluded that caustic ingestion represents a serious condition where prevention is the key. Once a child suffers an injury, rapid and careful evaluation of the injury with endoscopy, and a course of close observation and dilations if needed, will often avoid esophageal replacement. When necessary, the stomach is the best first option if it is viable, followed by the colon, and finally, the jejunum.